THE EFFECT OF BRIDGING EXERCISE AND GAIT INTERVENTION FOR HEMIPARASE AFTER STROKE ISCHEMIC AT PROF. DR. MARGONO SOEKARJO HOSPITAL PURWOKERTO: A CASE REPORT - Pradani, Frita Aulia; Naufal, Adnan Faris; Wijayaningsih, Anteng (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Stroke is a disease of functional brain disorders in the form of paralysis of the nerves that causes muscle weakness or imbalance, reduced postural control, muscle flexibility, and body asymmetry. As many as 80% of stroke patients will experience walking problems. Lack of muscle use for a long time can also cause secondary changes in muscles and nerves, causing musculoskeletal problems in the joints and problems coordinating activities in the neuromuscular system which is responsible for limb control and balance. The provision of bridging exercise and gait interventions can improve dynamic balance, leg muscle strength, walking speed and mobility after stroke so that it will also increase the patient's functional activity. Case Presentation: A 60-year-old housewife with a history of left hemiparase complains of dizziness, stiffness in the back area and feels heavy when trying to stand up since having a stroke 5 months ago. From the results of the examination, it was found that there was weakness in the lower extremities, balance disorders and disturbances in walking patterns. The patient has a history of hypertension and diabetes mellitus and a family history of similar diseases. Management and Outcome : Giving bridging exercise and gait intervention to patients aims to overcome problems in patients, especially strengthening the muscles of the lower extremities. From the results of measurements and examinations using BBS and NKT there was an increase in muscle strength and balance in patients. Discussion: Disorders of balance and gait patterns are often found in cases of hemiparase after a stroke. This is due to a decrease in strength in the core muscles and lower extremity muscles due to stroke, therefore it is necessary to reactivate these muscles so that the body can function properly. In the study, it was found that giving bridging exercise and gait intervention can activate core muscles and leg muscles so that there is an increase in these muscles. This can improve balance and change in the pattern of walking for the better. Conclusion: In this case, it was found that there was an increase in balance, leg muscle strength and stride length after the intervention of Bridging Exercise and Gait Intervention every 2 weeks for one month.